Aggressive plaque modification with rotational atherectomy and cutting balloon for optimal stent expansion in calcified lesions - Tang, Zhe; Bai, Jing; Su, Shao-Ping; Lee, Pui-Wai; Peng, Liang; Zhang, Tao; Sun, Ting; Nong, Jing-Guo; Li, Tian-De; Wang, Yu (Journal of geriatric cardiology : JGC, 2016)
Objective To evaluate the factors affecting optimal stentt expansion in calcified lesions treated by aggressive plaque modification with rotational atherectomy （RA） and a cutting balloon （CB）. Methods From January 2014 to May 2015, 92 patients with moderate to severe coronary calcified lesions underwent rotational atherectomy and intravascular ultrasound imaging at Chinese PLA General Hospital （Beijing, China） were included in this study, They were divided into a rotational artherectomy combined with cutting balloon （RACB） group （46 patients treated with RA followed by CB angioplasty） and an RA group （46 patients treated with RA followed by plain balloon angioplasty）. Another 40 patients with similar severity of their calcified lesions treated with plain old balloon angioplasty （POBA） were de- mographically matched to the other groups and defined as the POBA group. All patients received a drug-eluting stent after plaque prepara- tion. Lumen diameter and lumen diameter stenosis （LDS） were measured by quantitative coronary angiography at baseline, after RA, after dilatation, and after stenting. Optimal stent expansion was defined as the final LDS 〈 10%. Results The initial and post-RA LDS values were similar among the three groups. However, after dilatation, the LDS significantly decreased in the RACB group （from 54.5% ± 8.9% to 36.1%＋ 7.1%） but only moderately decreased （from 55.7% ± 7.8% to 46.9% ± 9.4%） in the RA group （time × group, P 〈 0.001）. After stenting, there was a higher rate of optimal stent expansion in the RACB group （71.7% in the RACB group, 54.5% in the RA group, and 15% in the POBA group, P 〈 0.001）, and the final LDS was significantly diminished in the RACB group compared to the other two groups （6.0% ± 2.3%, 10.8% ± 3.3%, 12.7% ± 2.1%, P 〈 0.001）. Moreover, an LDS 〈 40% after plaque preparation （OR = 2.994, 95% CI： 1.297-6.911） was associated with optimal stent expansion, which also had a positive correlation with the appearance of a calcified ring split （r = 0,581, P 〈 0.001）. Conclusions Aggressive plaque modification with RA and CB achieve more optimal stent expansion. An LDS ≤ 40% after plaque modification was a predictive factor for optimal stent expansion in calcified lesions. This parameter was also associated with the presence of calcified ring split.